Design and Simulation Application of 1 MWp Capacity Rooftop Distributed Solar Power Plant - Turan, Onur (Fırat University, 2022)
Photovoltaic (PV) power plants, which are one of the most important renewable energy sources, provide great opportunities in terms of clean energy, due to their almost zero harmful environmental impact and relatively easy installation, considering the solar potential of our country. In addition, the government supports offered within the scope of the Renewable Energy Resources Support Mechanism (YEKDEM) offers great opportunities to bring renewable energy resources into the economy. According to the projection made in the annual program of the Presidency of our country, an increase of 1000 MW is expected in the amount of electricity produced from solar power plants in 2022. In addition, the share of electricity produced by solar energy in the total production is expected to be 8.5%. In this study; the design and simulation application of a rooftop, grid-connected distributed solar power plant with a capacity of 1MWp was presented through the PVsyst program. In the study, it was seen that the panel slope, the right PV module, and inverter selection are extremely important. The annual amount of energy that can be supplied to the grid has been obtained as 1246 MWh. In the simulation studies, it was emphasized that such a facility, which was established compared to a power plant with equivalent energy production, would contribute positively to the impact of climate change by not emitting 14000 tons of Co2. It has been observed that revenue of 4,485,600 ? can be obtained from such a newly established facility for the first ten-year period with a fixed fee purchase guarantee with the domestic contribution. Considering that the life of the power plant will be 25 years, it can be said that the facility investment will be extremely advantageous even without YEKDEM support.

Yenilenebilir enerji kaynaklarının en önemlilerinden biri olan fotovoltaik (PV) santraller neredeyse sıfıra yakın olan zararlı çevresel etkisi ve nispeten kolay kurulumları nedeniyle, ülkemizin güneş potansiyeli de göz önünde bulundurulduğunda temiz enerji anlamında büyük fırsatlar sağlamaktadır. Ayrıca Yenilenebilir Enerji Kaynakları Destekleme Mekanizması (YEKDEM) kapsamında sunulan devlet destekleri yenilenebilir enerji kaynaklarının ekonomiye kazandırılması yönünde büyük fırsatlar sunmaktadır. Ülkemiz Cumhurbaşkanlığı yıllık programında yaptığı projeksiyona göre 2022 yılında güneş enerji santrallerinden üretilen elektrik miktarında 1000 MW artış beklenmektedir. Ayrıca güneş enerjisiyle üretilen elektriğin toplam üretim içerisindeki payının %8,5 olması öngörülmektedir. Bu çalışmada; 1MWp kapasiteye sahip çatı tipi, şebekeye bağlı dağıtık güneş enerji santralinin tasarımı ve simülasyon uygulaması PVsyst programı aracılığıyla sunulmuştur. Yapılan çalışmada panel eğimi, doğru PV modül ve inverter seçiminin son derece önemli olduğu görülmüştür. Yıllık şebekeye verilebilecek enerji miktarı 1246 MWh olarak elde edilmiştir. Yapılan simülasyon çalışmalarında eşdeğer enerji üretimine sahip bir elektrik santraline nazaran kurulan böyle bir tesisin 14000 ton ?Co?_2 salınımı yapmayarak iklim değişikliği etkisine olumlu katkı sunacağı vurgulanmıştır. Yeni kurulacak böyle bir tesisten ilk on yıllık süre boyunca yerli katkı ile birlikte sabit ücretle alım garantisiyle 4.485.600 ? gelir elde edilebileceği görülmüştür. Santralin ömrünün 25 yıl olacağı düşünüldüğündeyse YEKDEM destekleri olmasa bile tesis yatırımının son derece avantajlı olacağı söylenebilir.
1 MWp Kapasiteli Çatı Tipi Dağıtık Güneş Enerji Santralinin Tasarımı ve Simülasyon Uygulaması
Keywords: Engineering; Mühendislik